EFFECTIVENESS OF REFLEXOLOGY ON HEMIPARESIS MUSCLE STRENGTH FOR STROKE PATIENTS IN PUSKESMAS GULUK – GULUK, SUMENEP REGENCY - Kuzzairi Kuzzairi; Endang Fauziyah Susilawati (Jurnal Kesehatan Mesencephalon, 2022)
There are several treatments for hemiparesis stroke patients, namely medical treatment (conventional) and complementary alternative medicine. So far, in rural areas treating hemiparase stroke patients prefer complementary alternative treatments in the form of reflexology, namely massaging the hands, feet and other body parts by focusing on the nerves of the body. The purpose of this study was to determine the effectiveness of reflexology on hemiparesis muscle strength in stroke patients in the working area of the Puskesmas Guluk-guluk, Sumenep Regency. In this study using analytical methods. The variables in this study consisted of pre-test variables, namely muscle strength before being given reflexology and post-test variables, namely hemiparesis muscle strength after reflexology. The technique of collecting data is purposive sampling in getting 5 respondents. With research data using muscle strength observation sheets with data processing editing, scoring, coding, tabulating, and statistical tests using SPSS. The results of the output test statistics in the Mann-Whitney test found that the asymmp.sig (2-tailed) value in the upper and lower extremities of 0.007 is smaller than the probability value of 005.  Based on the results of the p-value, there are differences in the results of muscle strength before reflexology and after reflexology. Because there is a significant difference, reflexology is effective in increasing the hemiparesis muscle strength of stroke patients. Therefore, good family support is needed for stroke patients in the rehabilitation phase who experience hemiparesis so that reflexology is carried out regularly.Keywords: Reflexology, Muscle strength, Hemiparesis